(untitled) (International Journal of Engineering and Computer Science, 2017)
People use various social network sites for different purposes. Social networks provide an important source of information regarding users and their interactions which is very valuable for identifying the identical users and recommender systems. In this survey paper we aims to address the identical user identification problem and recommending friends based on lifestyle of the users in social networking sites (SNS). A methodology called MOdeling Behaviour for Identifying Users across Sites (MOBIUS) is used for finding a mapping among identities of individuals in social media sites. Recommender systems or recommendation systems are a subclass of information filtering system that search for to predict the ’preference’ or ’rating’ that a user would give to an person/item/place/thing. Social Networking services focuses towards suggesting friends based on Users Social Graph or Geolocation based, which does not take user‟s liking, disliking etc. This survey also investigates about an app that utilizes the information of the user and makes recommendations by considering user‟s point of interest and calculating the similarities between each user, thus recommending the friends to the user in heterogeneous sites.